(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the main mechanisms and pedagogical directions for increasing student motivation in a digital learning environment. The study examines the impact of gamification, adaptive learning systems, interactive content, and social interaction methods on motivation. The article concludes with practical recommendations for teachers and educational institutions.